2014
DOI: 10.1111/napa.12056
|View full text |Cite
|
Sign up to set email alerts
|

A World of Suffering? Biocultural Approaches to Fat Stigma in the Global Contexts of the Obesity Epidemic

Abstract: Even as obesity rates rise, weight-related stigma remains widespread in the UnitedOne of the most striking human biological trends of recent decades has been massive globalization of overweight and obesity. Two-thirds of all people live in countries where overnutrition kills more people than undernutrition (World Health Organization [WHO] 2013). Substantive scientific evidence points to the critical role of interrelated structural factors such as poverty, food systems, work patterns, and the built environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…Recent research has established that obesity-related stigma is increasingly reported in many lower-income, developing countries throughout the globe (Brewis, 2011;Brewis and Wutich, 2014;Council and Placek, 2014), a concerning trend that seems to have emerged and accelerated over the last decade. The goal here is to identify if weight-related stigma may also be an emergent contributor to depressive symptoms in lower-income countries, as it is already known to be in high-income ones.…”
Section: Introductionmentioning
confidence: 98%
“…Recent research has established that obesity-related stigma is increasingly reported in many lower-income, developing countries throughout the globe (Brewis, 2011;Brewis and Wutich, 2014;Council and Placek, 2014), a concerning trend that seems to have emerged and accelerated over the last decade. The goal here is to identify if weight-related stigma may also be an emergent contributor to depressive symptoms in lower-income countries, as it is already known to be in high-income ones.…”
Section: Introductionmentioning
confidence: 98%
“…A parallel development has been reported for weight-related stigmatization: prejudice towards individuals with excess body weight is spreading worldwide, even in cultures that were conventionally understood to show no to little weight-related stigmatization (Brewis et al 2011). Nevertheless, the extent of prejudice still varies between cultural groups (Brewis and Wutich 2014;Hebl et al 2009;Pepper and Ruiz 2007;Puhl et al 2015).…”
Section: Introductionmentioning
confidence: 77%
“…En sciences humaines et sociales, les corps obèses ont rarement été envisagés dans leur dimension physique. Parmi les courants dominants, un premier réunit un ensemble de travaux menés sur le processus de stigmatisation et sur les situations de discrimination auxquelles sont susceptibles de faire face les personnes obèses (Brewis & Wutich, 2014;Carof, 2015). D'inspiration foucaldienne, un second s'attache à analyser de façon critique les discours issus de la santé publique en mettant notamment en évidence leur dimension normative et moralisatrice (Bossy & Briatte, 2011;Génolini & Clément, 2010;Lutz, 2017).…”
Section: Explosion Du Cadre Théorique Initialunclassified